Isu Hukum Dalam Penanganan Pandemi: Evaluasi Respons Hukum Terhadap Krisis Kesehatan di Indonesia - Warsito, Ronggo; Oktafianur, Muhammad Dodi; F, Ferdiyansyah; Azizah, Tiara Putri (Media Hukum Indonesia (MHI), 2024)
To handle the health crisis more effectively, increased transparency and accountability in decision making and policy implementation are needed. This includes providing clear and open information to the public about the steps taken by the government, as well as mechanisms for evaluating and reporting progress in handling the crisis. Active Community Participation: The community must be actively involved in the decision-making process and implementation of policies related to the health crisis. This includes listening to community aspirations and needs, as well as exploring local knowledge and available resources to strengthen crisis management efforts. Inter-Agency Collaboration and Stakeholder Engagement Close collaboration between various government agencies, the private sector, non-governmental organizations and civil society is essential to respond effectively to the health crisis. This includes good coordination in the distribution of resources and responsibilities between institutions, as well as the formation of strategic partnerships to support crisis management efforts. Capacity Strengthening and Training: Health officials and policy implementers should be trained regularly on laws, policies and practices related to health crises. This includes increasing understanding of health protocols, law enforcement procedures, and ethical principles in responding to health crises. Continuous Evaluation and Learning Continuous evaluation of the government's response to the health crisis.